Consumers’ Healthy Lifestyle: Does It Matter For The Consumption Pattern Of Healthy Food? - Farouk Djermani; Yaty Sulaiman; Nik Kamariah Nik Mat; Muhammad Amsal Sahban (Jurnal Aplikasi Manajemen, Ekonomi dan Bisnis, 2020)
Unhealthy food consumption has been linked to the risk of many diseases such as non-communicable disease and obesity. The objective of this paper is to identify the influencing factors that determine the consumption patterns of healthy food among academician in the northern part of Malaysia and its causal relationships using a theoretical model based on the Stimuli’s organism response theory. A quantitative research design approach was selected where the questionnaire was formulated for primary data collection Data were collected from 360 respondents in Malaysia by using systematic random sampling and subjected to Smart PLS analysis. The proposed model fits the data well by having good validity and reliability. The results revealed that the consumer healthy lifestyle fully mediated the relationship between promotion, place and the consumption pattern of healthy food. Finally, implications and recommendations of these findings are discussed.